תשוקה מינית בספר חנוך א' ועידוד בברית החדשה להתנזרות מינית - ניר, רבקה (מחשבת ישראל, 2021)
This article claims that according to the Book of the Watchers in 1 Enoch, the sin of the angels is not only in copulating with the daughters of men, but also in bringing sexual desire to the world. Sex had already existed beforehand, but without sexual desire. This conception, which has parallels in the Qumran Scrolls as well as in the Pseudepigrapha, influenced Christian tradition. In the NT letters, the sin of the angels comes up several times, invariably in a sexual context, and Christian believers are presented as new angels who are called to put this sin to death. But the most explicit comparison of Christians to angels is provided by the synoptic Gospels: ‘For in the resurrection, they neither marry nor are given in marriage, but are like angels in heaven’ (Matthew 22:30 and par.). The development of this Christian ideal is backgrounded by the tradition of the angels’ sin in Enoch: instead of the fallen angels who left heaven and brought sexual desire to the world, the new angels will utterly abstain from sex and sexual desire, and dwell in heaven forever. Thus, sexual abstinence is conceived as a means to eschatological redemption.